Olivers Twisted: Urban Milieu from Text to Media - Mario Martino (Cahiers Victoriens et Edouardiens)
This paper focuses on two transpositions of Oliver Twist: Oliver!, by Carol Reed, and the Walt Disney cartoon Oliver & Company, both of which are musicals. Both films underscore a crucial interest in the urban milieu and enthusiastically explore it, stressing an optimistic culmination in happy ending. Crucial to this perspective, one of the major structural devices of Oliver! is its division into two halves, each beginning in a splendid view of city life, its teeming vitality, richness, and variety of trades: an alluring setting to the orphan’s symbolic rebirths. Oliver & Company, emphasizing the fairy-tale elements of the novel, draws on Reed’s optimistic perception, with contemporary New York replacing nineteenth-century London. Strolling the city, the abandoned kitten Oliver is lectured by Dodger to be ‘street smart’ . . . /to ‘get a New York City heart.’